Promoting social inclusion in the early years of elementary school: a focus on children's epistemic beliefs for moral reasoning. Issue 5 (4th May 2017) - Scholes, Laura; Lunn Brownlee, Jo; Walker, Susan; Johansson, Eva; Lawson, Veronica; Mascadri, Julia
ABSTRACT: As classrooms continue to diversify, there is an increasing need to understand children's inclusive behaviours and moral reasoning. Research shows that epistemic beliefs (beliefs about knowing and knowledge) can influence reasoning for adults, but we know little about this relationship in younger children or how classroom contexts relate to epistemic beliefs for moral reasoning. Thirty-one elementary school children (mean age 6.5 years) participated in epistemic beliefs and moral reasoning tasks in the first year of a three-year longitudinal study. Findings showed that while children described objectivist epistemic beliefs (right/wrong answers) about social inclusion, their justifications revealed an unexpected, more complex set of epistemic beliefs. Implications for moral pedagogies are discussed.